Digital Technologies as External Enablers of New Venture Creation in the IT Hardware Sector. (January 2018) - von Briel, Frederik; Davidsson, Per; Recker, Jan
We develop theory about how and when digital technologies enable new venture creation processes. We identify two fundamental properties of digital technologies—specificity and relationality—and develop propositions that link these properties to six enabling mechanisms: compression, conservation, expansion, substitution, combination, and generation. We use the linked properties and mechanisms to determine how and when in the venture creation process—from prospecting to developing to exploiting—digital technologies have enabled start-ups in the IT hardware sector and develop stage-dependent propositions about their sector-level effects. We conclude our theorizing by discussing its implications beyond digital technologies and the IT hardware sector.